Management and prognosis of primary tracheal cancer: A national analysis. (19th July 2013) - Nouraei, S. Mahmoud; Middleton, Steve E.; Reza Nouraei, S. A.; Virk, Jagdeep S.; George, P. Jeremy; Hayward, Martin; Sandhu, Guri S.
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis To perform a national review of the incidence and treatment of primary tracheal cancer and to identify gaps in service provision and factors associated with survival. Study Design Retrospective analysis of Hospital Episode Statistics data for England between 1996 and 2011. Methods Information about age, sex, morbidity, provider trust, diagnostic delay, nature of hospital admission and treatment, and palliation‐free survival were recorded. The relationship between variables and survival was explored with Cox regression. Results There were 874 patients, giving an incidence of 0.9 per million. Mean age at diagnosis was 66 ± 13, and there were 456 (52%) males. Mean presentation to diagnosis latency was 2.5 ± 8 months, and 40% of patients presented as emergency admissions. There were 19 cases of oesophageal involvement and 241 cases of bronchopulmonary involvement; and 188 patients developed distant metastases. There were 60 curative resections (6.9%), which was the most significant predictor of palliation‐free survival (hazard ratio: 0.23; 95% confidence interval 0.13–0.38). Other prognostic variables included age, sex, emergency admission, interventional bronchoscopy, chemotherapy, oesophageal involvement, and distant metastases. Ten‐year palliation‐free survival was 60.8% with curative resection and 19.5% overall. Eighty‐six percent of patients were treated in units that treated fewer than one patient per year. Conclusion Tracheal cancer is under‐recognized and under‐treated. Early diagnosis, access to interventional bronchoscopy, and surgical treatment in specialist units may improve the survival of patients with this condition. Level of Evidence 4. Laryngoscope, 124:145–150, 2014